2019
DOI: 10.7150/ijbs.25783
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroloquinoline Quinone Prevents Estrogen Deficiency-Induced Osteoporosis by Inhibiting Oxidative Stress and Osteocyte Senescence

Abstract: Accumulating studies have shown that oxidative stress increases with aging, which is related to the pathophysiology of postmenopausal osteoporosis. Pyrroloquinoline quinone (PQQ) is a natural anti-oxidant with anti-oxidative and anti-aging effects. However, it is unclear whether PQQ has a protective role against estrogen deficiency-induced osteoporosis. Here, we evaluated the efficacy of PQQ on bone mineral density, bone microarchitecture, bone turnover and biomechanical strength in ovariectomy (OVX)-induced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 49 publications
7
90
1
Order By: Relevance
“…Comelekoglu et al found that BMD was reduced in 14% of OVX rats compared to control rats [29]. Moreover, accumulated evidences proved that osteoporosis was usually accompanied by weight gain [30,31]. Similar to these reports, we found that the body weight of OVX rats was elevated without altering food intake.…”
Section: Discussionsupporting
confidence: 87%
“…Comelekoglu et al found that BMD was reduced in 14% of OVX rats compared to control rats [29]. Moreover, accumulated evidences proved that osteoporosis was usually accompanied by weight gain [30,31]. Similar to these reports, we found that the body weight of OVX rats was elevated without altering food intake.…”
Section: Discussionsupporting
confidence: 87%
“…1 Oxidative stress (OS) plays an important role in decreasing osteogenic differentiation in cell lines and the bone mineral density during age-related osteoporosis. 2,3 Plasma antioxidant levels significantly decrease in women with age-related osteoporosis. 4 Mesenchymal stem cells (MSCs) can induce repair processes at sites of injury in vivo by replenishing bone cells, including chondrocytes and osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring plant-based compounds have been known to harbor therapeutic properties including osteogenesis. Phytoestrogens, which are naturally occurring non-steroidal plant compounds, are especially good candidates given their ability to exert beneficial agonistic effects on alleviating menopausal symptoms and bone loss ( Dutertre and Smith, 2000 ; Lv et al, 2018 ; Geng et al, 2019 ; Zhou et al, 2020 ), without increasing estrogenic cancer risks ( Adlercreutz, 2002 ; Horn-Ross et al, 2003 ; Anderson et al, 2013 ; Yang et al, 2019 ). Reports on the osteogenic agonism of individual phytoestrogens have been varied, ranging from strong agonism to antagonism with induction of adipogenesis even for the same compound despite the structural similarity to estrogen ( Dang and Lowik, 2005 ).…”
Section: Introductionmentioning
confidence: 99%